2004
DOI: 10.1007/s00125-004-1594-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of mannan-binding lectin in type 1 diabetic patients with incipient and overt nephropathy

Abstract: Aims/hypothesis: Diabetic nephropathy is associated with insulin resistance, and low-grade inflammation and activation of the complement system may contribute to this cascade. Mannan-binding lectin (MBL) activates the complement system, and elevated MBL concentrations have been observed in normoalbuminuric type 1 diabetic patients. The aim of this study was to assess whether MBL is associated with diabetic nephropathy in type 1 diabetes, and whether there is an association between MBL and low-grade inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
70
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 18 publications
10
70
3
Order By: Relevance
“…The association between MBL and diabetic nephropathy has been observed in several clinical studies (2)(3)(4)(5)(6)(7)(8). Also, the MBL2 genotype in the present cohort was marginally unequally distributed between patients with or without diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The association between MBL and diabetic nephropathy has been observed in several clinical studies (2)(3)(4)(5)(6)(7)(8). Also, the MBL2 genotype in the present cohort was marginally unequally distributed between patients with or without diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have demonstrated the close association between the lectin pathway of complement activation and diabetic nephropathy. In particular, high concentrations of the carbohydrate pattern-recognition molecule mannan-binding lectin (MBL), which initiates complement activation, are linked to diabetic nephropathy defined by urinary albumin excretion rate (2)(3)(4)(5)(6)(7)(8). In the present cohort, we previously showed the cross-sectional association between MBL2 genotype and diabetic nephropathy (2).…”
mentioning
confidence: 56%
“…These observations seem to contradict recent articles describing increased MBL concentrations in patients with type 1 diabetes with microvascular complications [29][30][31][32][33]. However, MBL plays a dual role in modifying inflammatory responses to injury [34].…”
Section: Discussionmentioning
confidence: 70%
“…In these studies, MBL levels correlated with UAE within the normal range, but not with metabolic control. The serum MBL levels were increased in microalbuminuric type 1 diabetic patients when compared with normoalbuminuric patients [6]. Diabetic nephropathy was more prevalent among type 1 diabetic patients with a high MBL expression genotype and high circulating MBL levels than among patients with a low MBL genotype and low serum MBL levels [5].…”
Section: Discussionmentioning
confidence: 89%
“…Under normal conditions MBL does not bind to the body's own structures, but it does possess potential self-reactive properties. A significant association between serum MBL levels and renal function has been reported in normoalbuminuric, microalbuminuric and macroalbuminuric type 1 diabetic patients [4][5][6]. Furthermore, in a cohort study of type 1 diabetic patients followed for 18 years from diagnosis, serum MBL was a significant predictor of later renal impairment.…”
mentioning
confidence: 90%